Structural and optoelectronic properties of NiTiX and CoVX (X = Sb and Sn) half-Heusler compounds: An ab initio study - Ameri, M.; Touia, A.; Khenata, R.; Yarub, Al - Douri; Baltache, H.b (Elsevier GmbH., 2013)
Link to publisher's homepage at http://www.elsevier.com/